Long-lived Anatexis in the Exhumed Middle Crust from the Torngat Orogen and Eastern Core Zone: Constraints from Geochronology, Petrochronology, and Phase Equilibria Modeling - Charette, Benoit (University of Waterloo, 2016)
The Torngat Orogen (southeastern Churchill Province, Canada) is a transpressional Paleoproterozoic orogen resulting from the collision between the North Atlantic Craton and the Core Zone (an Archean micro-continent) during the larger-scale Trans-Hudson Orogeny. The doubly-vergent Torngat Orogen is mainly exposed as granulite-facies metamorphic rocks and migmatites within a narrow (~150 km) belt. High-T metamorphic mineral assemblages (sillimanite stability field) are regionally overprinted by amphibolite-facies, high-strain, strike-slip shear zones. The development of granulite-facies metamorphic conditions, extensive anatexis, and intense shear deformation in such a narrow region is anomalous even for transpressional and hot orogens (such as Paleoproterozoic orogens during the “Archean-type” to “modern-type” tectonic transition). Recent field observations indicate that anatexis also occurred in the adjacent eastern Core Zone, thus shedding doubt on the true spatial extent of Torngat metamorphism and therefore on the dimensions and shape of the orogen. Here, thermobarometry, phase equilibria modeling, and geochronology were used to investigate the timing, extent, and significance of metamorphism in the western Torngat Orogen and eastern Core Zone. The results reveal that the Torngat Orogen is larger, older, and longer-lived than previously thought. Multi-equilibria thermobarometry and phase equilibria modeling highlight a continuous increase in metamorphic conditions from the Core Zone to the Torngat granulites with no evidence of a major metamorphic break. Close-to-peak metamorphic conditions, constrained from mafic samples, gradually increases from 8.7 kbars-814°C to 10.8 kbars-914°C from west to east. Melt crystallization conditions, defined from metasedimentary rock samples, are estimated at 5.4 kbars-709°C to 8.1 kbars-823°C from west to east. Rocks from the Core Zone and Torngat Orogen appear to have followed hairpin P-T paths in the sillimanite stability field. Metamorphic zircon U-Pb ages, monazite U-Pb ...